Golf implements and memorabilia : Eighteen holes of golf history. - McGimpsey, Kevin; Neech, David (London : Philip Wilson Publishers, 1999)
This edition teaches the basic skills for all track and field events, including a chapter devoted solely to race walking. Gerry Carr emphasizes learning the events in a series of progressions, from the most basic elements to the more advanced concepts
Includes bibliographical references (p. 158) and index.
Keywords: Golf